Characterization of disability following traumatic through knee and transfemoral amputations. Issue 6 (June 2018) - Tennent, David J.; Polfer, Elizabeth M.; Sgromolo, Nicole M.; Krueger, Chad A.; Potter, Benjamin K.
Abstract: Introduction: The purpose of this study is to characterize through knee and transfemoral amputations following severe traumatic injuries. Methods: A retrospective review of all transfemoral and through knee amputations sustained by United States military service members from 1 October 2001 to 30 July 2011 was conducted. Data from the Department of Defense Trauma Registry, the Armed Forces Health Longitudinal Technology Application, inpatient medical records and the Physical Evaluation Board Liaison Offices were queried in order to obtain characteristics related to injury sustained, demographics, treatment, and disability/mental health outcome data. Results: A total of 1631 amputations in 1315 patients were identified. Of these there were 37 through knee and 296 were transfemoral amputations. Adequate records for detailed analysis were available on 140 and 25 transfemoral and through knee amputations respectively. There were no significant differences in demographic information, injury mechanism, initial injury severity score, or associated injuries, to include contralateral amputations. There was no significant difference in average disability rating (67.9% vs 78.3%, p = 0.46) or number of service members determined to be fully disabled (42.2% vs 28.6% p = 0.33) between the transfemoral and through knee amputation groups. Whereas there was no difference between groups preoperatively, the knee disarticulation group displayed a higher rate of mental health diagnoses post-amputation (96% vs 72%, p < 0.001) and a higher preponderance of anxiety related disorders than the transfemoral amputees (26.92% vs 12.96%, p = 0.0129). Discussion/conclusion: Among this military amputee through knee and transfemoral amputees displayed similar physical disability profiles. However, the through knee amputees displayed a higher level of anxiety related disorders and mental health diagnosis overall. While we don't believe this relationship to be causal in nature, this finding reflects the importance of paying particular attention to mental health in the final disposition of traumatic lower extremity amputees.